A case study evaluation of the factors affecting fresh produce traceability. (5th April 2010) - Manikas, Ioannis; Manos, Basil; Vlachopoulou, Maro; Manthou, Vassiliki
This paper examines the different approaches given in literature on the factors that influence the efficiency of traceability in the agri-food sector in a particular fresh produce supply chain. An empirical research was conducted, which enables a more descriptive and exploratory approach. The technique used in this research was semi-structured in depth interviews with key personnel from each firm. Lack of vertical integration is observed in the particular supply chain. Ephemeral dynamic collaborations prevail, not allowing information flow transparency. Multi fragmentation is evident in all levels of the supply chain. Most of the transactions are based on personal relations built with suppliers and customers, while e-communication and e-transactions act complementarily, if exist. This reveals a non-systematic approach towards essential supply chain activities such as information flow and traceability.